Multi-threaded approach in generating frequent itemset of Apriori algorithm based on trie data structure - Ade Hodijah; Urip Teguh Setijohatmo; Ghifari Munawar; Gita Suciana Ramadhanty (Universitas Ahmad Dahlan, 2022)
This research is about the application of multi-threaded and trie data structures to the support calculation problem in the Apriori algorithm. The support calculation results can search the association rule for market basket analysis problems. The support calculation process is a bottleneck process and can cause delays in the following process. This work observed five multi-threaded models based on Flynn’s taxonomy, which are single process, multiple data (SPMD), multiple process, single data (MPSD), multiple process, multiple data (MPMD), double SPMD first variant, and double SPMD second variant to shorten the processing time of the support calculation. In addition to the processing time, this works also consider the time difference between each multi-threaded model when the number of item variants increases. The time obtained from the experiment shows that the multi-threaded model that applies a double SPMD variant structure can perform almost three times faster than the multi-threaded model that applies the SPMD structure, MPMD structure, and combination of MPMD and SPMD based on the time difference of 5-itemsets and 10-itemsets experimental result.